Investigating the effect of femtosecond laser pulses on noscapine and curcumin cellular uptake and improving drug delivery in gastric cancer cells - Nastaran Kahrarian; Hossein Behboudi; Atoosa Sadat Arabanian; Abolfazl Abedi; Reza Massudi (Heliyon)
The MKN45 cell line, a type of gastric cancer cell, exhibits resistance to chemotherapy agents through various mechanisms. Curcumin and noscapine, two plant-derived anticancer compounds, exhibit selective cytotoxicity towards cancer cells. However, their bioavailability is poor both in vitro and in vivo. In this study, we used femtosecond laser pulses in the near-infrared region (central wavelength of 1040 nm) with a pulse duration of 200 fs, a beam diameter of 4 mm, and different pulse energies and average powers to perforate the plasma membrane. We standardized the necessary conditions while minimizing cellular necrosis. MKN45 cells were treated with 25–200 μM curcumin and noscapine for 24 h after irradiation with an optimized femtosecond laser exposure (40 mW, 40sec) or without irradiation. The MTT cell viability assay revealed that pre-treatment with femtosecond (fs) laser pulses significantly increased cellular sensitivity to the treatment. Overall, the findings suggest that fs laser pulses irradiation enhance the bioavailability of both curcumin and noscapine. The combined treatment of femtosecond laser pulses and drugs can improve the drug's efficacy and the overall treatment outcome.